A Research Study of the Jurists’ opinions regarding the Sale on Installments - Muhammad Tahir; Kareem Dad (Journal of Islamic and Religious Studies, 2017)
In Islamic Sharia, the usury is prohibited while the trade has been allowed. This ruling is very clear and transparent in sources of Sharia. From the emergence of Islam many means of financing have been continuing which have got new shapes and names in modern ages. Among these contracts, one is sale in installments. This type of transaction is a part of modern financing in which the object is sold on the condition of payments in installments. The price of the object remains more than the cash payment. This concept has been discussed by the jurists and they have presented their different views about the sale in installments. In Islamic Sharia, the usury is prohibited while the trade has been allowed. This ruling is very clear and transparent in sources of Sharia. From the emergence of Islam many means of financing have been continuing which have got new shapes and names in modern ages. Among these contracts, one is sale in installments. This type of transaction is a part of modern financing in which the object is sold on the condition of payments in installments. The price of the object remains more than the cash payment. This concept has been discussed by the jurists and they have presented their different views about the sale in installments.